Bruce Bronzan for State Assembly Fundraiser at Saroyan Theatre with Willie Brown - Watkins, Howard::::::::: (1984)
Dr. Jeffrey Stone, Dr. Janet Lapp, Bruce Bronzan, Tony Mastro, Dr. Jim Kratzer, Dr. Charles Oliver